(untitled) (Journal of the College of Basic Education, 2022)
Polymer metal complexes of poly vinyl cyclicacetal and Ni (II), Mn (II), Co (II) and Hg (II) were prepared from the reaction of PVA with formaldehyde and 4-chlorobenzaldeyde. It has been established that, the polymer and its metal complexes showed good activities against five pathogenic bacteria (Escherichia coli, Shigella dysentery, Klebsiella pneumonae, Staphylococcus aureus, Staphylococcus Albus) and two fungal (Aspergillus Niger, Yeast) for Poly Vinyl Formal (PVF) and Poly Vinyl Benzylidene (PVB). The polymer metal complexes showed higher activity than the free polymer. The order of increasing activities was polymer < pol-Mn < pol-Ni < pol-Co ˂ pol-Hg for both PVF and PVB. The ability of these compounds to show antimicrobial properties suggests that, they can be further evaluated for medicinal and/or environmental applications.